The Graduation approach for the reduction of extreme poverty: impact evaluation of Sembrando Oportunidades Familia por Familia in Paraguay (2019)
ural poverty, a widespread problem for the Paraguayan government over the last decade ¿as well as for other economies in the region-, led to the implementation, in 2016 and 2017, of the ¿Sembrando Oportunidades Familia por Familia¿ pilot program, an initiative based on the graduation approach to reduce the incidence of extreme poverty in rural areas. Evaluating the intervention results is essential to understand the effectiveness of this approach in reducing poverty in the Paraguayan context, where the government is in charge of its implementation. For this evaluation, an instrumental-variable impact evaluation and a results evaluation were conducted, showing significant positive changes in the treated households¿ productive capacity and savings behavior as well in their perception of wellbeing.  These results are useful for the design of a program that can help to effectively overcome extreme poverty in this and other developing countries. This exercise is part of the set of evaluations carried out by the Platform for Evaluation and Learning of the Graduation Program in Latin America (www.plataformagraduacionla.info).